'THE MOST DANGEROUS ENEMIES TO SHOPKEEPERS': EIGHTEENTH-CENTURY SHOPLIFTING IN THE ARCHIVE. Issue 2 (October 2019) - Tickell, Shelley
Abstract : The rapid growth in shop numbers in eighteenth-century England precipitated a wave of theft. Shoplifting became a major concern to retailers, who successfully lobbied to have it made a capital offence. Thousands of shoplifters were taken to court, particularly in London, and through their cases we can come to understand the nature of this fledgling crime. Pre-trial documents and commercially produced court reports vividly portray how it was perpetrated and how retailers responded to the threat. This paper describes the origin, availability and reliability of these sources, in particular assize court documents and the Proceedings of the Old Bailey. Their content discloses the nature of the threat shopkeepers faced, the tactics of those who sought to plunder their shops, and the inventiveness with which retailers devised countermeasures. A study of this 'darker side' of shopping in the archive reveals surprising synergies with modern shop-protection practices.